Impact of tissue microstructure on a model of cardiac electromechanics based on MRI data - Carapella, V (2013)
Cardiac motion is a highly complex and integrated process of vital importance as it sustains the primary function of the heart, that is pumping blood. Cardiac tissue microstructure, in particular the alignment of myocytes (also referred to as fibre direction) and their lateral organisation into laminae (or sheets), has been shown by both experimental and computational research to play an important role in the determination of cardiac motion patterns. However, current models of cardiac electromechanics, although already embedding structural information in the models equations, are not yet able to fully reproduce the connection between structural dynamics and cardiac deformation. The aim of this thesis was to develop an electromechanical modelling framework to investigate the impact of tissue structure on cardiac motion, focussing on left ventricular contraction in rat. The computational studies carried out were complemented with a preliminary validation study based on experimental data of tissue structure rearrangement during contraction from diffusion tensor MRI.